2013
DOI: 10.2478/intox-2013-0013
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity induced by iodine-131 in human cultured lymphocytes

Abstract: 131-radioiodine has been widely used as an effective radionuclide for treatment of patients with thyroid diseases. The purpose of this study was to investigate the genotoxic effects of iodine-131 in human cultured lymphocytes. Whole blood samples from human volunteers were incubated with iodine-131 (10, 50, 100 µCi/1.5ml) for 2 h. The lymphocytes were mitogenically stimulated to allow for evaluation of the number of micronuclei in cytokinesis-blocked binucleated cells. At the dose 100 µCi, iodine-131 induced g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…It concentrates in thyroid cells and kills tumor cells, yet it has several side effects such as sialadenitis, gastrointestinal symptoms, xerostomia, temporary bone-marrow suppression and neoplasia (Bushnell et al , 1992 , Noaparast et al , 2013 ). 131 I may also induce genetic damage and chromosomal instability in normal cells that may result in secondary malignancies (Baugnet-Mahieu et al , 1994 , Watanabe et al , 2004 , Hosseinimehr et al , 2013 ). The cytotoxic effect of 131 I is mainly related to beta particles.…”
Section: Introductionmentioning
confidence: 99%
“…It concentrates in thyroid cells and kills tumor cells, yet it has several side effects such as sialadenitis, gastrointestinal symptoms, xerostomia, temporary bone-marrow suppression and neoplasia (Bushnell et al , 1992 , Noaparast et al , 2013 ). 131 I may also induce genetic damage and chromosomal instability in normal cells that may result in secondary malignancies (Baugnet-Mahieu et al , 1994 , Watanabe et al , 2004 , Hosseinimehr et al , 2013 ). The cytotoxic effect of 131 I is mainly related to beta particles.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that 10 and 100 microcurie doses of I-131 increased the number of micronuclei 8.5 times more than the control group. [ 13 ] In another study, Eberlein et al . evaluated the DSBs caused by I-131 and Lu-137 and showed a linear relationship between the absorbed radiation dose and the number of DSBs.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 9 10 ] Furthermore, it may induce chromosomal instability and genetic damage in normal cells that may cause in secondary cancers. [ 11 12 13 ] The cellular damage resulting from I-131 can be through direct ionization or creation of reactive oxygen spaces. [ 14 ] One of the vital aims during the interaction between ionization radiations and the cells is the cell DNA in which can cause a range of damages such as single-strand break and double-strand break (DSB).…”
Section: Introductionmentioning
confidence: 99%
“…By the by, toxic effect on immune pathways could be elucidated (Guzik et al ., 2001). Genotoxicity testing of 131-radioiodine a drug used for treatment of patients with thyroid diseases with cultured human lymphocytes was recently described (Hosseinimehr et al ., 2013 ), as a work in predictive toxicology.…”
Section: Discussionmentioning
confidence: 99%